The complex relationship between arterial carbon dioxide levels and acute heart failure: implications for prognosis and management - Afifah, Yuri; Prasetya, Indra; Anjarwani, Setyasih; Pashira, Andranissa Amalia (Universitas Brawijaya, 2025)
Acute Heart Failure (AHF) can affect carbon dioxide levels in the body by altering the balance between ventilation and carbon dioxide production, leading to either hypocapnia or hypercapnia. Arterial carbon dioxide (CO2) levels are essential for maintaining respiratory function and acid-base balance. However, the relationship between arterial CO2 levels and AHF remains complex and not fully understood. Diverse factors affect arterial CO2 levels in patients with AHF, including neurohormonal activation, respiratory compensation for hypoxemia, and changes in pulmonary perfusion. Hypocapnia, characterized by low arterial CO2 levels (PaCO2 < 35 mmHg), is commonly observed in AHF due to hyperventilation-driven respiratory alkalosis secondary to pulmonary congestion. It showed a strong connection with the survival rates of patients following a cardiac arrest. Nevertheless, elevated levels of carbon dioxide in the blood, known as hypercapnia, with a partial pressure of arterial carbon dioxide (PaCO2) exceeding 45 mmHg, can also arise in the later phases of acute heart failure (AHF), indicating fatigue in respiratory muscles or deterioration in pulmonary edema. Abnormal arterial CO2 levels have been associated with increased morbidity and mortality in AHF patients, serving as a valuable prognostic marker.